Теоретико-методологічні підходи до оцінки конкурентоспроможності підприємств - Жовновач, Р. І.; Zhovnovach, R. (КНТУ, 2011)
В статті наведено теоретико-методологічні підходи до оцінки конкурентоспроможності підприємств. Встановлено об’єкт, мету, завдання та критерії визначення конкурентоспроможності підприємства залежно від суб’єктів її оцінювання. Представлено методику оцінки конкурентоспроможності підприємства. In the article theoretical and methodological approaches to the evaluation of enterprise’s competitiveness are given. The object, aim, tasks and criteria of the definition of enterprise’s competitiveness are formed according to the subjects of its evaluation. The procedure of evaluation of enterprise’s competitiveness is offered.
Theoretical and Methodological Approaches to the Evaluation of Enterprise’s Competitiveness
Keywords: конкурентоспроможність; рівень конкурентоспроможності; методи оцінки конкурентоспроможності